Application of Types of Learning Models Problem Based Learning (PBL) in Improving History Learning Results for Class XII MIA 9 SMA Negeri 3 Medan - Mandaliya, Pita; Nugraha, Muhammad Adika; Sihotang, Masniar (ALACRITY : Journal of Education, 2024)
This research uses classroom action research in its implementation. The subjects in this research are students of class XII MIA 9 SMA Negeri 3 Medan, and the population in this research are all students of class learning model problem based learning (PBL). The stages carried out in this research consisted of 2 cycles. This research was carried out using documentation techniques and providing tests in the form of pre-tests and post-tests, with the average score in cycle I being 89 then in cycle II being 94, and for learning completeness in cycle I 88.5% then learning completeness in cycle II 97.2%.